Efeito de Técnicas Osteopáticas Estruturais na Postura e Flexibilidade de Individuos com Escoliose Idiopática do Adolescente - Pelai, Elisa Bizetti [UNESP] (2014)
Given the high rate of progression of difficulty in treatment and lack of scientific proof of conservative physical therapy methods in Adolescent Idiopathic Scoliosis (AIS), the present study aimed to verify the effect of Osteopathy techniques in structural variables of posture and flexibility of subjects with AIS. METHODS: The study population consisted of 30 patients with AIS (Cobb angle ≥ 10), aged 18-25 years, of both genders. The sample was divided in Experimental Group (EG) (n = 15) or placebo (GP) (n = 15). For the measurement of spinal deformity of the Adams test was performed. The spinal curvatures (LCCe - cephalic cervical lordosis; LLCe - lumbar lordosis head; LCCa - caudal cervical lordosis and LLCa - caudal lumbar lordosis) were assessed using a slit adapted watermarked. Evaluating the flexibility of the posterior chain (Wells) and lateral flexibility test (lateral inclination of the trunk) was performed. To detect more rounded vertebra in NSR was held Scaning Quick Test and Mitchel. Tests Thumb Ascending Gillet and to evaluate the locked Iliac were performed...